The effectiveness of birthing ball exercise on reducing pain during the active phase of first stage labor - Lestari, Anita (ELECTRON (Journal of Science and Technology), 2024)
Pain is an unpleasant sensory and emotional experience commonly experienced during childbirth and is physiologically caused by distension of the lower uterine segment, cervical dilation, stretching of cervical tissues, and pressure on surrounding structures and nerves, which may lead to fear and anxiety and affect both the mother and the fetus. A preliminary survey conducted at BPM Utin Mulya, Pontianak City, reported approximately 300 deliveries in 2018, with most mothers experiencing severe pain in the abdomen, waist, back, and radiating to the spine. The birthing ball is a non-pharmacological pain management method that involves sitting on the ball and gently rocking back and forth to promote comfort and facilitate labor progression. This study aimed to analyze the effectiveness of birthing ball exercises in reducing pain during the active phase of the first stage of labor. A quasi-experimental design with a pretest–posttest non-equivalent control group was applied, involving 30 women in the active phase of the first stage of labor. The intervention group received birthing ball exercises, while the control group was given deep breathing relaxation. Data were analyzed using Wilcoxon and Mann–Whitney non-parametric tests. The results showed a significant reduction in pain scale in the birthing ball group after the intervention (p = 0.001), while the control group also showed a reduction after deep breathing relaxation (p = 0.046); however, the decrease in pain was greater in the birthing ball group. In conclusion, birthing ball exercises are more effective than deep breathing relaxation in reducing pain during the active phase of the first stage of labor.